Climate change and the macroeconomics of bank capital regulation - Francesco Giovanardi; Matthias Kaldorf (Deutsche Bundesbank, 2024)
This paper proposes a quantitative multi-sector DSGE model with bank failure and firm default to study the interactions between bank regulation and climate policy. Households value the liquidity of deposits, which are protected by deposit insurance. Banks collect deposits and issue equity to extend defaultable loans to clean and fossil energy firms. Bank capital regulation affects liquidity provision to households, bank risk-taking, and loan supply across sectors. Using a calibrated version of the model, we obtain four results: first, fossil penalizing capital requirements can be discarded as climate policy instrument, since their effect on sector-specific investment is quantitatively negligible in general equilibrium. Second, Ramsey-optimal capital requirements in response to a tax-induced clean transition decline to counteract negative loan demand effects. Third, differentiated capital requirements are only necessary if banks are not perfectly diversified across sectors. Fourth, nominal rigidities induce a temporary tightening of capital requirements if the transition is inflationary and, thus, spurs a boom on the loan market.
Keywords: E44; G21; G28; Q58; 330; Bank Regulation; Liquidity Provision; Risk-Taking; ClimatePolicy; Clean Transition; Multi-Sector Model